Analisis Postur Kerja Menggunakan Metode Rapid Entire Body Assesment (REBA) Proses Pembuatan Buis Beton - Darsini; Reza Tania Achmadi; Mathilda Sri Lestari (Indonesian Society of Applied Science, 2022)
There are quite a number of entrepreneurs making precast concrete in Polokarto sub-district, the community works as precast concrete making workers as their life support. The resulting production is in the form of Buis Concrete/Concrete Pipes. The process of making concrete buis, among others: the process of selecting materials, mixing process, lifting process, printing process, drying process. Activities carried out during the production process are carried out repeatedly, causing complaints to workers. These complaints arise due to non-ergonomic body postures causing pain in some parts of the body felt by workers. This study aims to determine the level of risk and the percentage of complaints felt during the process of making concrete buis. The methods used are Nordic Body Map (NBM), and Rapid Entire Body Assessment (REBA). The results of the research from the NBM questionnaire on the manufacture of concrete buis segemn workers' bodies experience complaints are the waist, back, right shoulder, right upper arm and right hand. Research using the REBA method has a risk level ranging from 7-10 so it includes a moderate to high level of risk that requires work posture action. Keywords: Concrete buis making, Work posture, NBM, REBA